COMPLICATIONS OF AUGMENTATION MAMMOPLASTY - I.V. SERGEEV; T.R. FAYZULLIN; D.P. LARIONOV (Avicenna Tajik State Medical University, 2020)
Augmentation mammoplasty is one of the most demanded and most frequently performed plastic surgeries in the world. The first breast augmentation using first-generation implants performed in 1962. Since, the surgery technique and the quality of implants have been improved. Although the number of complications significantly decreased, they still occur both in the early and the late postoperative periods. Often complications include seroma, hematoma, asymmetry, double bubble (double fold), implant displacement, rippling, capsular contracture, etc. The most formidable late complication described in 1997, is breast implant-associated anaplastic large cell lymphoma (BIA-ALCL), which is manifested more than after a year, by the formation of the late malignant seroma after implantation. A review of modern literature provides a clear idea of the number of received complications. However, the pathogenesis of the development of some of them (capsular contracture, implant-associated lymphoma) is still unclear, and therefore, further long-term studies are needed to obtain more accurate data.